Spatial distribution of introduced brook trout Salvelinus fontinalis (Salmonidae) within alpine lakes: evidences from a fish eradication campaign. Issue 1 (1st January 2017) - Tiberti, R.; Nelli, L.; Brighenti, S.; Iacobuzio, R.; Rolla, M.
Abstract: Brook trout Salvelinus fontinalis have been used worldwide to stock fishless alpine lakes, negatively affecting native biota. Understanding its spatial ecology in invaded ecosystems can provide information to interpret and contrast its ecological impact. We opportunistically used capture points of brook trout gillnetted during an eradication campaign to assess the distribution patterns of four unexploited populations inhabiting high-altitude lakes. The main eradication method implies the use of many gillnets with several mesh sizes, which are selective for different fish sizes. For each lake we drew six capture maps associated with as many different mesh sizes, and we tested whether the distance from the coastline (which in alpine lakes is a reliable proxy of the most important spatial gradients, e.g. depth, temperature, prey availability, lighting conditions) influences the proportion of captured fish belonging to different size classes and the number of fish captured by the nets with different mesh sizes. To interpret the results, we also provide a cartographic description of the lakes’ bathymetry and littoral microhabitats. We found (1) a negative relationship between brook trout distribution and the distance from the coastline in all of the size classes, lakes and mesh sizes; (2) that large brook trout can thrive in the lakes’ center, while small ones are limited to the littoral areas; and (3) that the distance from the coastline alone cannot explain all the differences in the catch densities in different parts of the lakes. As in their native range, introduced brook trout populations also have littoral habits. Microhabitats, prey availability and distance from the spawning ground are other likely factors determining the distribution patterns of brook trout populations introduced in alpine lakes. The obtained results also provide useful information on how to plan new eradication campaigns.